Physical-chemical analysis of underground water in the Coro plain: potential use for human consumption, irrigation and industry. A technical note - Parra, Yusmary; López Pérez, Julio; Valero, Gregorio (Rev. Téc. Fac. Ing. Univ. Zulia)
The Coro aquifer is located in a strip approximately 20 kms long lying between El Recreo (11Âº 22’N -69Âº 48’W) and Los Perozo (22Âº 25’N -69Âº 38’W) in the Municipality of Miranda, State of Falcón. The main physical and chemical properties of water samples collected in 1995 (dry and rainy season) from wells in the above and neighboring areas were analyzed with a view to determining whether or not the water could be used by humans, industry and for irrigation. In the case of the latter, it must be borne in mind that a certain degree of salinity could produce salinization of the land because of the high evaporation index, aided and abetted by the indiscriminate use of chemical fertilizers. The results are presented in terms of temperature, taste, color, pH, conductivity, total dissolved solids, sulfates, chloride, calcium, sodium, potassium and magnesium. In general, they show that the qualitative chemical composition is the same for the whole aquifer. However, quantitative variations were found even in neighboring wells: high concentrations of total dissolved solids. Especially of sulfate ions, chlorides and bicarbonates. The high salinity index, especially in El Cebollal and Los Perozo, indicate that the water from the Coro Plain aquifer could only be used for irrigation in permeable soils with good drainage and for salt-resistant crops. The water from the central region of the aquifer. Huertas Viejas de Coro and Los Perozo is of relatively better physical-chemical quality. Consequently, these would best be adapted for irrigation and greater use in industry but not, however, for human consumption.